Exposure to Acetylcholinesterase Inhibitors Alters the Physiology and Motor Function of Honeybees - Williamson, Sally M.; Moffat, Christopher; Gomersall, Martha; Saranzewa, Nastja; Connolly, Christopher; Wright, Geraldine A. (Frontiers in Physiology, 2013)
Cholinergic signalling is fundamental to neuro-muscular function in most organisms. Sub-lethal doses of neurotoxic pesticides that target cholinergic signalling can alter the behaviour of insects in subtle ways; their influence on non-target organisms may not be readily apparent in simple mortality studies. Beneficial arthropods such as honeybees perform sophisticated behavioural sequences during foraging that, if influenced by pesticides, could impair foraging success and reduce colony health. Here, we investigate the behavioural effects on honeybees of exposure to a selection of pesticides that target cholinergic signalling by inhibiting acetylcholinesterase (AChE). To examine how continued exposure to AChE inhibitors affected motor function, we fed adult foraging worker honeybees sub-lethal concentrations of these compounds in sucrose solution for 24 h. Using an assay for locomotion in bees, we scored walking, stopped, grooming, and upside down behaviour continuously for 15 min. At a 10nM concentration, all the AChE inhibitors caused similar effects on behaviour, notably increased grooming activity and changes in the frequency of bouts of behaviour such as head grooming. Coumaphos caused dose-dependent effects on locomotion as well as grooming behaviour, and a 1µM concentration of coumaphos induced symptoms of malaise such as abdomen grooming and defecation. Biochemical assays confirmed that the 4 compounds we assayed (coumaphos, aldicarb, chlorpyrifos, and donepezil) or their metabolites acted as AChE inhibitors in bees. Furthermore, we show that transcript expression levels of two honeybee acetylcholinesterase inhibitors were selectively upregulated in the brain and in gut tissues in response to AChE inhibitor exposure. The results of our study imply that the effects of pesticides that rely on this mode of action have subtle yet profound effects on physiological effects on behaviour that could lead to reduced survival.